Kesalahan Berbahasa Indonesia pada Penulisan Media Luar Ruang di Kecamatan Mesuji Makmur - Mulyanto Widodo; Dedi Febriyanto (Institut Agama Islam Negeri Curup, 2022)
Facts on the ground show that there are still many mistakes in the practice of speaking Indonesian in the community. The Indonesian language errors in question include errors in the oral and written realms. In the realm of writing, Indonesian language errors are often found in outdoor media, such as posters and bulletin boards. This study aims to describe errors in Indonesian in writing outdoor media in Mesuji Makmur District. The research was conducted using a qualitative descriptive method. The data in this study are in the form of words, sentences, or discourses that are obtained directly in the field through various outdoor media, such as posters, bulletin boards, stretch cloth, and similar media in the Mesuji Makmur sub-district. As for analyzing the data, the following steps were used; (1) data reduction, (2) data presentation, (3) temporary conclusion drawing, and (4) verification. The results showed various forms of language errors were found in the writing of outdoor media in the Mesuji Makmur sub-district. The errors in question include; (1) spelling errors, (2) word choice errors, (3) morphological errors, and (4) errors in the use of prepositions